1998
DOI: 10.1073/pnas.95.3.818
|View full text |Cite
|
Sign up to set email alerts
|

The representation of the ipsilateral visual field in human cerebral cortex

Abstract: Previous studies of cortical retinotopy focused on influences from the contralateral visual field, because ascending inputs to cortex are known to be crossed. Here, functional magnetic resonance imaging was used to demonstrate and analyze an ipsilateral representation in human visual cortex. Moving stimuli, in a range of ipsilateral visual field locations, revealed activity: (i) along the vertical meridian in retinotopic (presumably lower-tier) areas; and (ii) in two large branches anterior to that, in presump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
146
2
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(182 citation statements)
references
References 43 publications
31
146
2
3
Order By: Relevance
“…Negative responses are found in the most foveal and peripheral parts of the response curves. This could indicate the presence of mechanisms generating a negative BOLD response (Tootell et al, 1998;Shmuel et al, 2002;Smith et al, 2004). In principle, this effect could mask small signals associated with the putative filling-in process.…”
Section: Resultsmentioning
confidence: 99%
“…Negative responses are found in the most foveal and peripheral parts of the response curves. This could indicate the presence of mechanisms generating a negative BOLD response (Tootell et al, 1998;Shmuel et al, 2002;Smith et al, 2004). In principle, this effect could mask small signals associated with the putative filling-in process.…”
Section: Resultsmentioning
confidence: 99%
“…There are also no callosal connections between the quadrants in V1 and V2 (26). Thus, the behavioral and neural integration we observed must reflect either feedback from higher cortical areas with bilateral receptive fields (35) or indirect subcortical connections (16). To test the latter hypothesis, we examined activity in the superior colliculus and the pulvinar, identified anatomically according to criteria described in ref.…”
Section: Resultsmentioning
confidence: 99%
“…These results were replicated by DeYoe et al (1996) and Engel et al (1997), also utilizing a cortical surface-based analysis but manually distinguishing the borders based on polar-angle information. Further phase-encoded mapping studies with modifications of the stimulus revealed visual areas V3A (DeYoe et al, 1996;Tootell et al, 1997Tootell et al, , 1998c, V3B (Press et al, 2001;Smith et al, 1998), V7 (Mendola et al, 1999;Press et al, 2001;Tootell et al, 1998a,c;Tootell and Hadjikhani, 2001), V8 , a putative homologue of the lateral intraparietal area (LIP) (Sereno et al, 2001), and retinotopic organization in human MT/V5 (Huk et al, 2002).…”
Section: Introductionmentioning
confidence: 99%